An Overview on Ethnopharmacology of Different Medicinal Plants of Odisha State of India in the Management of Diabetes Mellitus - Rath, Deepankar; pattnaik, Gurudutta; Kar, Biswakanth (Asian Journal of Chemistry, 2021)
Diabetes mellitus, commonly known as diabetes, is a group of metabolic disorder associated with elevated blood glucose level. World health organization recommended the traditional and herbal remedies for the diabetic management. The application of herbal remedies is extremely increased worldwide in the last three decades. Most of the synthetic drugs were discovered from the plant source out of different regions of the world to meet the demand. Several medicinal plants like Gymnema sylvestre, Pterocarpus marsupium, Catharanthus roseus, Trigonella foenum, Annona squamosa, Aegle marmelos, Withania somnifera, Boerhavia diffusa, Boerhavia erecta, Momordica charantia, Cocos nucifera, Ricinus communis, Azadira chtaindica and Aloe vera have been reported to have varying level of hypoglycemic property. One of the factors involved in the evolution of diabetic convolutions is the impairment due to free radicals and hence a compound with antioxidant and antidiabetic potential would be more effective. The present review article was designed to provide an absolute data on these medicinal plant based remedies by using the traditional healers of Odisha state, India.